Manganese-based layered perovskite solid–solid phase change material: Synthesis, characterization and thermal stability study. (August 2019) - Raj, Cyril Reuben; Suresh, S.; Bhavsar, R.R.; Singh, Vivek Kumar; Reddy, A. Sarath; Upadhyay, Arijit
Highlights: Synthesis of layered perovskite SS-PCM with manganese as base metal, for thermal energy storage system by chemical method. Characterization, comparison study of (1-Cn H2n+1 NH3 )2 MnCl4 with ( n = 9, 10) for low temperature energy storage application. Layered perovskite possess excellent thermal stability and thermal cycling effect were compared at 0, 500 and 1000 cycles through FTIR, DSC and TGA. Layered perovskite holds excellent thermal property and energy storage density with sharp increase in thermophysical property during phase transition. Abstract: In this paper, a new class of Manganese based Layered Perovskite Solid–Solid Phase Change Materials (1-C9 H19 NH3 )2 MnCl4 and (1-C10 H21 NH3 )2 MnCl4 (SS-PCM) were synthesized by a liquid phase reaction method, and the effect of thermal cycling was compared for 0, 500, 1000 cycles. The crystal morphology, elemental compositions, thermal degradation, and phase transition phenomena were characterized and compared. It was noted from DSC that the phase transition temperatures and enthalpies upon heating and cooling for (1-C9 H19 NH3 )2 MnCl4 is 293.80 K, 64.75 kJ/kg, and 285.57 K, 65.49 kJ/kg, and for (1-C10 H21 NH3 )2 MnCl4 is 311.54 K, 73.83 kJ/kg, and 304.24 K, 79.79 kJ/kg, respectively. During the transition period, the synthesized material possesses increased thermal conductivity and thermal diffusivity which eliminates the need for thermal conductivity enhancers. Additionally, we found through characterization that the SS-PCMs were thermally and chemically stable for around 1000 cycles because of the presence of the metal substrate. Hence, the synthesized SS-PCMs are desirable for various low-temperature thermal energy storage applications.